THE THE ELEVENTH GRADE STUDENTS OF THE ISLAMIC SENIOR HIGH SCHOOL IN BONDOWOSO WILL BENEFIT FROM THE IMPLEMENTATION OF A PROBLEM-BASED LEARNING METHOD - Romadhona, Gina; Hayuningtyas, Nina (Critical Review of English-Arabic World Journal, 2023)
English is one of the important aspects to be mastered in this era. English also the most widely used language in various aspects of life, including science, education, business, economics, technology, entertainment, etc. English is not always the first language in some countries. There are several countries that make English as a second language and even a foreign language. Meanwhile, in Indonesia, English is still a foreign language. English as a foreign language, has entered the education curriculum in Indonesia since Indonesia reached its heyday. This research used Classroom Action Reseach as the research design. Classroom Action Research was a research that aimed to improve the quality of learning practice, that focused on the process of the teaching and learning in the class. As a result of research obtained, Classroom Action Research had been conducted in two cycle that consisting of 2 meetings and 1 meeting for the post test in every cycle. The result pointed out that the implementation of Problem Based Learning could improve students’ speaking skills in the Eleventh-grade G2 students of MAN Bondowoso. The results showed that the application of Problem Based Learning could improve the speaking skills of class XI G2 students of MAN Bondowoso.